Design and Implementation of "Handipum" WebRTC-based Conferencing Service in ASNET-AM Network - Arthur S. Petrosyan; Petrosyan, Gurgen S.; Robert N. Tadevosyan (Изд-во НАН РА)
This paper presents the results of research and deployment experience with design and implementation of the ASNET-AM WebRTC-based audio/video conferencing service, called "Handipum" (handipum.asnet.am). Since the WebRTC-services become widely used, this service can provide a modern browser-based conferencing environment for ASNET-AM users.
Keywords: Mathematics; Computer software